Explorando correções de van der Waals na descrição teórica de interações de H2O com materiais bidimensionais - Grison, Tulio Gnoatto (2024)
As the description of the forces present in physical systems improves, the weaker interactions become more relevant. Van der Waals (vdW) interactions are considered weak but far-reaching and are present in a wide range of phenomena, such as the adherence of amphibians to different surfaces, interactions between DNA molecules, and chemical reactions, among others. In addition, vdW interactions are involved in numerous fundamental processes for creating or improving technologies in different segments (e.g. gas sensors, drug transportation, optoelectronic devices). Many studies have shown that these interactions are relevant in describing interfaces between solid-liquid or solid-gas systems. On the other hand, they lack more general and precise theoretical descriptions. Density Functional Theory seeks to solve the many-electron problem by approximating the exchange and correlation functional. The existing functionals do not always reproduce the effects of vdW interactions, and there are many different ways of including them. In this study, we compare proposals for including the effects of vdW interactions in two systems containing anH2Omolecule interacting with monolayers of graphene or hexagonal boron nitride. We implemented the Grimme-D2 and Grimme-D3 corrections added to the PBE functional, and the vdW-DF functionals (by including or not the C09 exchange correction). We found that the corrections and vdW functionals had different effects on the systems studied, for example, to a greater or lesser extent, they decreased the distance and interaction energy compared to the PBE functional. Notable differences were found in the description of activation energies as a function of the different systems calculated for different corrections and functionals. In addition, we found a significant impact on the electronic properties of the systems. We conclude that the corrections evaluated here can significantly alter the results compared to the PBE functional. When including these approximations, one must be careful to ensure that the corrections or functionals reproduce the desired characteristics as accurately as possible.